Are trajectories of a syndemic index in adolescence linked to HIV vulnerability in emerging and young adulthood?. (20th February 2018) - Córdova, David; Heinze, Justin E.; Hsieh, Hsing-Fang; Mistry, Ritesh; Salas-Wright, Christopher P.; Cook, Stephanie H.; Zimmerman, Marc A.
Abstract : Objectives: To examine trajectories of adolescent psychosocial risk – drug use, depressive and anxiety symptoms, and violence victimization and observation – and the longitudinal relationship between psychosocial risk trajectories during adolescence and HIV risk behaviors in adulthood. Methods: The 18-year longitudinal study was conducted from September 1994 through May 2013, in Michigan. Eight hundred and fifty predominantly (80%) African-American adolescents completed demographics and measures of drug use, depressive and anxiety symptoms, violence victimization and observation at Times 1–4, sexual risk behaviors at Times 5 and 6, and social conditions (i.e. family, peer, and community-level factors) between 14.9 and 32.0 years of age. Results: Growth mixture modeling revealed two trajectories of psychosocial risk factors which can be characterized as a syndemic index: high-frequency and low-frequency. The high-frequency class was more likely to report HIV risk behaviors, including condomless sex at last sexual intercourse with their primary and secondary partner, sexual intercourse with someone they just met, at least four sexual partners, and licit and illicit drug use prior to sexual intercourse at Time 5 (mean age 23.1). At Time 6 (mean age 32.0), the high-frequency class was more likely to report sexual intercourse with someone they just met and at least four sexual partners, relative to the low-frequency class. In addition, the high-frequency class was linked to peer and family-level indicators of social conditions. Conclusion: A syndemic index comprised of co-occurring psychosocial risk factors in adolescence seem to have lasting effects on the vulnerability to engage in HIV risk behaviors in emerging adulthood, some of which extend into young adulthood.